2017
DOI: 10.1016/j.ridd.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Using personal construct methodology to explore relationships with adolescents with Autism Spectrum Disorder

Abstract: Whilst this exploratory study highlighted some commonality in terms of perceptions of family support and friendships as protective and desirable, participants differed in their ability to establish and maintain peer relationships. Participants valued personal qualities such as intelligence, humour and trust within relationships, and recognised the important role of peers and siblings in the development of social skills, a finding which has implications for the delivery of social skills training and other inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Study samples focused on children with disabilities [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], children with and without disabilities [66][67][68][69], as well as children without disabilities [70][71][72]. The type of disabilities or conditions included physical disabilities, cerebral palsy, Down syndrome, autism spectrum disorders (including Asperger's syndrome, as previously classified in the DSM-IV [73]), intellectual disabilities, learning disabilities, attention-deficit/hyperactivity disorder, Noonan syndrome, brain injury, Spina bifida, cystic fibrosis, post meningococcal disease, severe asthma, and tracheostomy.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study samples focused on children with disabilities [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], children with and without disabilities [66][67][68][69], as well as children without disabilities [70][71][72]. The type of disabilities or conditions included physical disabilities, cerebral palsy, Down syndrome, autism spectrum disorders (including Asperger's syndrome, as previously classified in the DSM-IV [73]), intellectual disabilities, learning disabilities, attention-deficit/hyperactivity disorder, Noonan syndrome, brain injury, Spina bifida, cystic fibrosis, post meningococcal disease, severe asthma, and tracheostomy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The type of disabilities or conditions included physical disabilities, cerebral palsy, Down syndrome, autism spectrum disorders (including Asperger's syndrome, as previously classified in the DSM-IV [73]), intellectual disabilities, learning disabilities, attention-deficit/hyperactivity disorder, Noonan syndrome, brain injury, Spina bifida, cystic fibrosis, post meningococcal disease, severe asthma, and tracheostomy. Study participants were preschoolers [50,62,67,69], primary-school-aged children [46,[48][49][50][51][55][56][57][58]60,65,66,[68][69][70]72], and secondary school-aged adolescents [48,50,52,54,56,59,61,65,66,[69][70][71]. Only five studies involved recruitment of participants from the community [47,53,59,63,64], whereas all others were conducted in the school setting.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside these "functional" modes of treatment, it is broadly recognized that the emotional aspects of the autistic condition call for psychotherapy, and various modes of "emotional" therapy focus on the inner reality of the child, the development of the self, the child's attempts to express him/herself, his/her anxieties, inhibitions, defenses, and the way in which she/he perceives and experiences the world. Most of the research on ASD relates to psychotherapies, such as personal construct theories, family-focused therapy, and cognitive behavioral therapy (CBT; Hare, 1997;Cardaciotto and Herbert, 2004;Wood et al, 2015;Murphy et al, 2017;Storch et al, 2020). CBT takes center stage in research with ASD and numerous randomized controlled trials (RCTs) have shown that it is effective for treating anxiety disorders in adults, adolescents, and in children diagnosed with ASD (Sukhodolsky et al, 2013;Hesselmark et al, 2014;Vasa et al, 2014;Spain et al, 2015;Wood et al, 2015).…”
Section: Dir -A Developmental Approach Developed By Stanleymentioning
confidence: 99%